Longitudinal associations between stress and sleep disturbances during COVID‐19. (28th March 2022) - Ballesio, Andrea; Zagaria, Andrea; Musetti, Alessandro; Lenzo, Vittorio; Palagini, Laura; Quattropani, Maria Catena; Vegni, Elena; Bonazza, Federica; Filosa, Maria; Manari, Tommaso; Freda, Maria Francesca; Saita, Emanuela; et al.
Abstract: The psychological consequences of COVID‐19 pandemic may include the activation of stress systems, that involve the hypothalamic‐pituitary‐adrenal axis which influences many physiological functions, including sleep. Despite epidemiological studies evidenced greater prevalence of stress symptoms and sleep disturbances during COVID‐19, longitudinal evidence investigating the effects of stress on sleep disturbances during the pandemic is lacking. We collected measures of perceived stress and sleep disturbances during the first wave of COVID‐19 (March 2020) and at 8–10 months follow up in a sample of 648 adults ( M  = 33.52, SD = 12.98 years). Results showed that 39.4% of participants reported moderate to extremely severe stress in March 2020. Prevalence of sleep disturbances was 54.8% in March 2020 and 57.4% at follow‐up. Structural equation modelling highlighted that perceived stress in March 2020 significantly predicted sleep disturbances at follow up ( β  = 0.203; p  < 0.001), even after controlling for baseline sleep disturbances. Results remained significant even after controlling for the effects of covariates including age, sex, depression and anxiety symptoms, and referring to psychological services ( β  = 0.179; p  < 0.05). Findings confirm the high prevalence of stress symptoms during the COVID‐19 pandemic and provide first longitudinal evidence for the effects of perceived stress on sleep disturbances during the pandemic.